Non-Revenue Water in Intermittent and Continuous Water Service in South India - Jayaramu, K. P.; Kumar, B. Manoj (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
Non-revenue water (NRW) is prevalent in developing countries' cities, necessitating immediate intervention. In parts of Hubli-Dharwad in India, a study was conducted to assess NRW in one of the intermittent water service (IWS) pilot area and in newly constructed continuous water service (CWS) demonstration zone under World Bank assistance. The purpose of the study is to assess NRW and identify opportunities to improve service levels. This paper book chapter elaborates assessment of NRW in IWS and CWS areas of Hubli city in South India. According to the study, the NRW in IWS can reach 37 percent, while it is only about 15 percent in CWS. The outcome of this study will be helpful in existing intermittent water service and CWS scaling up projects in India and developing countries.